Metal halide embedded metal-organic framework based ammonia adsorbents

KR1020260133776APending Publication Date: 2026-09-04KOREA UNIV RES & BUSINESS FOUND
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
KR1020260038435
Authority / Receiving Office
KR · KR
Patent Type
Applications
Current Assignee / Owner
Priority Date
2025-02-28
Filing Date
2026-03-03
Publication Date
2026-09-04

Smart Images

  • Figure PAT00003_ABST
    Figure PAT00003_ABST
Patent Text Reader

Abstract

The present invention relates to a metal-organic framework-based ammonia adsorbent in which a metal halide is dispersed. According to the present invention, by introducing a metal halide into the pores or on the surface of a porous metal-organic framework, stepwise adsorption behavior resulting from the formation of a complex between ammonia and the metal halide is induced, thereby enabling high ammonia storage capacity. Furthermore, since the complexation reaction can proceed reversibly at a relatively low temperature, low-temperature desorption is possible, and structural stability can be maintained even during the repeated adsorption and desorption processes of ammonia by controlling the expansion of the metal halide by the porous metal-organic framework. Therefore, the ammonia adsorbent of the present invention can be usefully utilized as a large-capacity ammonia storage medium.
Need to check novelty before this filing date? Find Prior Art

Description

Technology Field

[0001] The present invention relates to a metal-organic framework-based ammonia adsorbent in which a metal halide is dispersed. Background Technology

[0002] As the transition to a hydrogen economy utilizing hydrogen as a primary energy source accelerates, the importance of technologies capable of efficiently and economically storing and transporting hydrogen is increasing. In this context, ammonia is attracting attention as a substance with high potential for use as a hydrogen storage medium, energy carrier, and industrial raw material.

[0003] Ammonia has a hydrogen storage density of approximately 108 g L per unit volume. -1 As, liquid hydrogen (approx. 71 g L) -1 It has the advantage of having a higher hydrogen density than hydrogen and being capable of liquefying under relatively mild conditions (approx. -33°C, 1 atm). Due to these characteristics, ammonia has high potential for use as a large-scale hydrogen transport medium.

[0004] However, ammonia is corrosive and toxic, and presents problems such as low storage density in the gaseous state and the requirement of high pressure or low temperature conditions for liquefied storage. These conditions can lead to increased facility costs and a burden on safety management. Therefore, solid adsorbent-based storage technology capable of safely storing ammonia under ambient temperature and pressure conditions is being proposed as an alternative.

[0005] Metal halides can exhibit high ammonia storage capacity by forming metal-ammine complexes with ammonia and have the advantage of being able to desorb at relatively low temperatures. However, the ammonia adsorption process may be accompanied by changes in lattice structure and significant volume expansion, which may lead to reduced structural stability upon repeated use or impose limitations on their application as large-capacity storage devices.

[0006] Meanwhile, metal-organic frameworks (MOFs) have a high specific surface area and a controllable pore structure, and exhibit excellent adsorption characteristics by forming Lewis acid-base interactions with ammonia through open metal sites. However, there are disadvantages such as the requirement of a relatively high temperature of 150-250°C for ammonia desorption and the potential for structural collapse during repeated adsorption and desorption processes.

[0007] Therefore, there is a need to develop a new type of ammonia adsorbent that maintains structural stability after ammonia adsorption, suppresses excessive volume expansion, and enables low-temperature desorption for economical operation. The problem to be solved

[0008] The present invention has been devised to solve the aforementioned problems, and the objective of the present invention is to provide an ammonia adsorbent and an ammonia storage system including the same, which can be usefully utilized as a large-capacity ammonia storage body by significantly improving ammonia adsorption performance through the introduction of a metal halide, enabling low-temperature desorption after ammonia adsorption, maintaining structural stability and suppressing volume expansion even after ammonia adsorption. means of solving the problem

[0009] In order to solve the above problem, the present invention,

[0010] An ammonia adsorbent is provided comprising: a porous metal-organic framework; and a metal halide introduced into the pores or on the surface of the porous metal-organic framework.

[0011] According to the present invention, the porous metal-organic framework may be selected from the group consisting of M2(dobpdc), M2(dobdc), M2(m-dobdc), M2(dondc) and M2(dotpdc):

[0012] Here, metal M is Mg, Ti, V, Cr, Mn, Fe, Co, Ni, Cu or Zn, dobpdc is 4,4'-dioxido-3,3'-biphenyldicarboxylate, dobdc is 2,5-dioxido-1,4-benzenedicarboxylate, m-dobdc is 4,6-dioxido-1,3-benzenedicarboxylate, dondc is 1,5-dioxido-2,6-naphthalenedicarboxylate, and dotpdc is 4,4'-dioxido-3,3'-triphenyldicarboxylate.

[0013] According to the present invention, the porous metal-organic framework may be selected from the group consisting of MIL-100, MIL-101, MIL-121, MIL-127, MIL-53, UiO-66, and UiO-67.

[0014] According to the present invention, the metal halide may be an alkali metal halide.

[0015] At this time, the alkali metal may be one or more selected from the group consisting of lithium (Li), sodium (Na), potassium (K), rubidium (Rb), and cesium (Cs).

[0016] According to the present invention, the content of the metal halide may be 30 to 70 weight%.

[0017] According to the present invention, the ammonia adsorbent can exhibit stepwise adsorption behavior induced by the formation of a complex between ammonia and a metal halide.

[0019] The present invention also provides an ammonia storage system comprising the ammonia adsorbent.

[0021] The features and advantages of the present invention will become more apparent from the following detailed description based on the accompanying drawings.

[0022] Prior to this, terms and words used in this specification and claims shall not be interpreted in their ordinary and dictionary meanings, but must be interpreted in a meaning and concept consistent with the technical spirit of the invention, based on the principle that the inventor may appropriately define the concept of the terms to best describe his invention. Effects of the invention

[0023] According to the present invention, by introducing a metal halide into the pores or on the surface of a porous metal-organic framework, stepwise adsorption behavior resulting from the formation of a complex between ammonia and the metal halide is induced, thereby enabling high ammonia storage capacity. Furthermore, since the complexation reaction can proceed reversibly at a relatively low temperature, low-temperature desorption is possible, and structural stability can be maintained even during the repeated adsorption and desorption processes of ammonia by controlling the expansion of the metal halide by the porous metal-organic framework. Therefore, the ammonia adsorbent of the present invention can be usefully utilized as a large-capacity ammonia storage medium. Brief explanation of the drawing

[0024] Figure 1 shows the synthesis process of LiCl@M2(dobpdc). Figure 2 shows the PXRD pattern of LiCl@M2(dobpdc)-5, LiCl. Figure 3 shows M2(dobpdc), LiCl@M2(dobpdc)-5, MeOH-washed LiCl@M2(dobpdc)-5 (M=Mg 2+ , Mn 2+ , Co 2+ , Ni 2+ This represents the PXRD pattern of ). Figure 4 shows the survey scan spectrum of LiCl@M2(dobpdc)-5. Figure 5 shows the Mg 1s, C 1s, O 1s, Li 1s, and Cl 2p narrow scan spectra of Mg2(dobpdc) and LiCl@Mg2(dobpdc)-5. Figure 6 shows the Mn 2p, C 1s, O 1s, Li 1s, and Cl 2p narrow scan spectra of Mn2(dobpdc) and LiCl@Mn2(dobpdc)-5. Figure 7 shows the Co 2p, C 1s, O 1s, Li 1s, and Cl 2p narrow scan spectra of Co2(dobpdc) and LiCl@Co2(dobpdc)-5. Figure 8 shows the Ni 2p, C 1s, O 1s, Li 1s, and Cl 2p narrow scan spectra of Ni2(dobpdc) and LiCl@Ni2(dobpdc)-5. Figure 9 shows the results of measuring the thermal stability of Mg2(dobpdc), LiCl@Mg2(dobpdc)-5, Mn2(dobpdc), LiCl@Mn2(dobpdc)-5, Co2(dobpdc), LiCl@Co2(dobpdc)-5, Ni2(dobpdc), and LiCl@Ni2(dobpdc)-5. Figure 10 shows the nitrogen adsorption isotherms of LiCl@Mg2(dobpdc)-5, LiCl@Mn2(dobpdc)-5, LiCl@Co2(dobpdc)-5, and LiCl@Ni2(dobpdc)-5, as well as the pore distribution of Mg2(dobpdc) and LiCl@Mg2(dobpdc)-5 calculated from the nitrogen isotherms. Figure 11 shows the PXRD patterns of Mg2(dobpdc), LiCl@Mg2(dobpdc)-3, LiCl@Mg2(dobpdc)-5, LiCl@Mg2(dobpdc)-7, and LiCl. Figure 12 shows the elemental mapping images of C, O, Mg, and Cl using STEM-EDS of LiCl@Mg2(dobpdc)-3, LiCl@Mg2(dobpdc)-5, and LiCl@Mg2(dobpdc)-7. Figure 13 shows the HRTEM image, Fast Fourier transform (FFT) pattern, and SAED pattern of LiCl@Mg2(dobpdc)-5. Figure 14 shows the nitrogen adsorption isotherms of LiCl@Mg2(dobpdc)-3, LiCl@Mg2(dobpdc)-5, and LiCl@Mg2(dobpdc)-7, and the pore distribution of LiCl@Mg2(dobpdc)-3 and LiCl@Mg2(dobpdc)-7 calculated from the nitrogen isotherms. Figure 15 shows the 298 K ammonia adsorption isotherms of LiCl@Mg2(dobpdc)-5, LiCl@Mn2(dobpdc)-5, LiCl@Co2(dobpdc)-5, LiCl@Ni2(dobpdc)-5, and LiCl. Figure 16 shows the 273K ammonia adsorption isotherm of LiCl@Mg2(dobpdc)-5, LiCl. Figure 17 shows an optical image of the volume change of LiCl@Mg2(dobpdc)-5, LiCl at 273K after ammonia injection. Figure 18 shows the 273 K ammonia adsorption isotherms of LiCl@Mg2(dobpdc)-3, LiCl@Mg2(dobpdc)-5, and LiCl@Mg2(dobpdc)-7. Figure 19 shows the repeated adsorption and desorption ammonia adsorption isotherm of LiCl@Mg2(dobpdc)-5 (left) and the amount of ammonia adsorbed at 1 bar (right). Figure 20 shows the correlation of volume-weight ammonia storage capacity of LiCl@Mg2(dobpdc)-5 and the reported adsorbent (left), and the indirect weight-weight hydrogen storage capacity of LiCl@Mg2(dobpdc)-5 and the reported adsorbent (right). Figure 21 shows the repeated cycle breakthrough curve of LiCl@Mg2(dobpdc)-5. Figure 22 shows the PXRD patterns of (left) Mg2(dobpdc)_G and (right) LiCl@Mg2(dobpdc)_G-5. Figure 23 shows the 298 K ammonia adsorption isotherm of LiCl@Mg2(dobpdc)_G-5. Figure 24 shows the ammonia adsorption isotherms at 298 K for LiCl@MOF-74(Mg)-5, LiCl@MIL-101(Cr)-5, and LiCl@UiO-66(Zr)-5. Specific details for implementing the invention

[0025] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by a skilled expert in the art to which this invention pertains. In general, the nomenclature used herein is well known and commonly used in the art.

[0027] The present invention aims to provide an ammonia adsorbent and an ammonia storage system comprising the same, wherein the ammonia adsorption performance is significantly improved through the introduction of a metal halide, low-temperature desorption is possible after ammonia adsorption, structural stability is maintained and volume expansion is suppressed even after ammonia adsorption, and the adsorbent can be usefully utilized as a large-capacity ammonia storage body.

[0028] To this end, the present invention provides an ammonia adsorbent comprising: a porous metal-organic framework; and a metal halide introduced into the pores or on the surface of the porous metal-organic framework.

[0029] In this specification, "introduction" is a concept including physical support, penetration into pores, surface immobilization, partial coordination bonding, or a dispersed state.

[0030] The porous metal-organic framework according to the present invention may be selected from the group consisting of M2(dobpdc), M2(dobdc), M2(m-dobdc), M2(dondc), and M2(dotpdc). In this case, the metal M may be Mg, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, or Zn, and preferably may be Mg, Mn, Co, or Ni. In addition, dobpdc is 4,4'-deoxydo-3,3'-biphenyldicarboxylate, dobdc is 2,5-deoxydo-1,4-benzenedicarboxylate, m-dobdc is 4,6-deoxydo-1,3-benzenedicarboxylate, dondc is 1,5-dioxide-2,6-naphthalenedicarboxylate, and dotpdc is 4,4'-deoxydo-3,3'-triphenyldicarboxylate, and can be represented by the following [organic skeletal group].

[0031] [Organic Skeletal Group]

[0032]

[0033] In addition, the porous metal-organic framework according to the present invention may be selected from the group consisting of MIL-100, MIL-101, MIL-121, MIL-127, MIL-53, UiO-66, and UiO-67.

[0034] The metal halide according to the present invention may be any metal-ammine complex capable of forming with ammonia, and specifically, the metal halide may be an alkali metal halide.

[0035] At this time, the alkali metal may be one or more selected from the group consisting of lithium (Li), sodium (Na), potassium (K), rubidium (Rb) and cesium (Cs), and the halide may be chloride, bromide, or iodide.

[0036] The metal halide according to the present invention may preferably be lithium chloride (LiCl).

[0037] In addition to the metal halide used in the present invention, metal hydrides and metal borohydrides may be introduced, wherein the metal hydrides may be LiH, NaH, KH, MgH2, CaH2, LaNi5H6, MgNiH4, and the metal borohydrides may be LiBH4, NaBH4, KBH4, Mg(BH4)2, Ca(BH4)2, Al(BH4)3, Ti(BH4)3.

[0039] The present invention can exhibit stepwise adsorption behavior induced by the formation of a metal-ammine complex between ammonia and the metal halide through the introduction of the metal halide, thereby enabling high ammonia storage capacity. Furthermore, since the complexation reaction can proceed reversibly at a relatively low temperature, low-temperature desorption of ammonia is possible, and the porous metal-organic framework spatially limits the expansion of the metal halide, thereby maintaining structural stability and suppressing volume expansion even after ammonia adsorption.

[0040] At this time, as can be seen from the results of the following examples, the content of the introduced metal halide is preferably 30 to 70 weight% based on the total weight of the ammonia adsorbent, and more preferably 40 to 65 weight%. If the content of the metal halide is below the lower limit, the number of active sites contributing to the complexing reaction formed within the pores is insufficient, so stepwise adsorption behavior may not be clearly observed, and the effect of increasing ammonia storage capacity may be limited. On the other hand, if it exceeds the upper limit, the excess metal halide may partially block the pore channels or aggregate and distribute, thereby hindering gas diffusion and reducing the effective pore volume, which may lower the ammonia adsorption efficiency. Therefore, it is desirable to control the content of the metal halide within the above range, thereby achieving a balance between securing active sites contributing to the complexing reaction and maintaining the pore structure.

[0041] The present invention also provides an ammonia storage system comprising the ammonia adsorbent. For example, the ammonia storage system may include a storage container for receiving the ammonia adsorbent and a flow path for filling and discharging ammonia, and may be configured to store ammonia in an adsorbed state under atmospheric pressure or pressurized conditions, and to desorb ammonia through heating or depressurization when necessary.

[0043] [Example]

[0044] The present invention will be described in more detail below through examples. These examples are solely for illustrating the present invention, and it will be obvious to those skilled in the art that the scope of the present invention is not to be interpreted as being limited by these examples. Accordingly, the actual scope of the present invention is defined by the appended claims and their equivalents.

[0046] Metal-organic framework LiCl@M with introduced lithium chloride nanoparticles 2 Manufacturing of (dobpdc)

[0047] The metal-organic framework incorporating metal halide nanoparticles according to the present invention was prepared via a wet impregnation method. Specifically, 3 M, 5 M, and 7 M LiCl methanol solutions were prepared by dissolving lithium chloride (LiCl) in methanol, respectively. Meanwhile, M2(dobpdc)(M= Mg 2+ , Mn 2+ , Co 2+ , Ni 2+ The sample was activated at 180°C under vacuum conditions for 12 hours to remove residual solvent within the pores. The purpose of this activation process was to open the pores so that the metal halide could be effectively introduced into the pores. Subsequently, 10 mL of the LiCl methanol solution and 100 mg of activated M2(dobpdc) were quantitatively added to a 20 mL glass vial. A magnetic stirrer was placed in the mixed solution and stirred at room temperature for 3 hours to introduce LiCl into the pores and surfaces of the metal-organic framework. After the reaction was completed, the resulting solid was recovered by filtration and vacuum dried for at least 12 hours to remove residual solvent. The obtained solid was sealed and stored (Fig. 1). The complexes obtained according to the molar concentration of the LiCl solution used were named LiCl@M2(dobpdc)-3, LiCl@M2(dobpdc)-5, and LiCl@M2(dobpdc)-7, respectively.

[0049] LiCl@M 2 Characterization of (dobpdc)

[0050] Figure 2 shows the Powder X-ray Diffraction (PXRD) patterns of LiCl@M2(dobpdc)-5 and LiCl, and Figure 3 shows M2(dobpdc), LiCl@M2(dobpdc)-5, and MeOH-washed LiCl@M2(dobpdc)-5 (M= Mg 2+ , Mn 2+ , Co 2+ , Ni2+ This represents the PXRD pattern of ).

[0051] According to the results in Fig. 2, characteristic diffraction peaks of lithium chloride were observed in the LiCl@M2(dobpdc)-5 sample, indicating the presence of LiCl within the metal-organic framework. Meanwhile, as confirmed in Fig. 3, the sample with introduced LiCl showed a tendency for the intensity of the characteristic diffraction peaks of the framework to decrease relatively compared to pure M2(dobpdc). This is interpreted as a change in X-ray scattering contrast caused by the LiCl introduced into the pores, or a partial decrease in diffraction intensity due to the filling effect within the pores. However, in the PXRD pattern re-measured after washing the sample with methanol (MeOH) to remove LiCl, the characteristic diffraction peaks of M2(dobpdc) appeared distinctly again, confirming that the crystallinity of the initial framework was restored. Through these results, it was confirmed that the structure of the framework does not collapse during the LiCl introduction process, that lithium chloride is physically introduced into the pores, and that the introduction and removal of LiCl can be performed reversibly.

[0053] Next, changes in chemical composition and binding energy after the introduction of LiCl were analyzed using X-ray photoelectron spectroscopy (XPS), and the results are shown in Figures 4 to 8.

[0054] Figure 4 shows the survey scan spectrum of LiCl@M₂(dobpdc)-5. In the spectrum above, Li 1s and Cl 2p signals were clearly observed, confirming that LiCl is present in the skeletal structure.

[0055] Figures 5 to 8 show the narrow scan spectra of Mg2(dobpdc), LiCl@Mg2(dobpdc)-5 (Fig. 5), Mn2(dobpdc), LiCl@Mn2(dobpdc)-5 (Fig. 6), Co2(dobpdc), LiCl@Co2(dobpdc)-5 (Fig. 7), Ni2(dobpdc), and LiCl@Ni2(dobpdc)-5 (Fig. 8), respectively.

[0056] The analysis results showed that after the introduction of LiCl, the binding energies of Mg 1s, Mn 2p, Co 2p, and Ni 2p tended to shift to a binding energy region approximately 0.2 to 0.5 eV lower. This decrease in binding energy is due to the high electronegativity of Cl - Metal ions (M) by 2+ This is due to the increased electron density of ), and through this, this is the open metal site of each framework and Cl - It was confirmed that there is an interaction between them.

[0057] Also, Mg 2+ , Mn 2+ , Ni 2+ In the case of, it maintains a 2+ oxidation state both before and after introduction, whereas Co 2+ In the case of Co in the 2p region after the introduction of LiCl, Co 2+ In addition to the peak corresponding to Co 3+ and Co 0 A signal attributed to was observed, implying that the Co-centered electronic environment was partially altered during the LiCl introduction process. Furthermore, deconvolution of the O 1s peak revealed an additional peak component corresponding to Li-O. Through this, Li + It was confirmed that it interacts with oxygen atoms in the framework and that LiCl does not merely exist physically but strongly interacts with metal nodes and the ligand environment.

[0059] Next, the thermal stability after the introduction of LiCl was evaluated by thermogravimetric analysis (TGA), and the results are shown in Figure 9 below. In addition, the mass ratio of the introduced LiCl was quantitatively analyzed using inductively coupled plasma atomic emission spectroscopy (ICP-AES), and the results are shown in Table 1 below.

[0060] Figure 9 shows the results of measuring the thermal stability of Mg2(dobpdc), LiCl@Mg2(dobpdc)-5, Mn2(dobpdc), LiCl@Mn2(dobpdc)-5, Co2(dobpdc), LiCl@Co2(dobpdc)-5, Ni2(dobpdc), and LiCl@Ni2(dobpdc)-5.

[0061] As shown in Figure 9, it was confirmed that when LiCl is introduced, the thermal stability increases somewhat because the LiCl present inside the pore partially stabilizes the skeletal structure or remains as an inorganic component during the pyrolysis process.

[0062] In addition, according to Table 1 below, the content of introduced LiCl was found to be distributed in the range of approximately 35 to 59 wt%. Even when using LiCl solutions of the same concentration, differences in the amount of LiCl introduced occurred depending on the type of metal, which is attributed to differences in the pore structure of each metal-organic framework, the electronic properties of the metal center, and the interaction with LiCl. Through these results, it was confirmed that LiCl can be successfully introduced into metal-organic frameworks and that the introduction behavior may vary depending on the type of metal.

[0063] Li [mmol L -1 ] M [mmol L -1 ] Li / M atomic ratio wt% LiCl LiCl@Mg2(dobpdc)-5 10270.57 2073.52 4.95 58.59 LiCl@Mn2(dobpdc)-5 9905.71 1776.03 5.58 41.33 LiCl@Co2(dobpdc)-5 7809.66 1502.15 5.20 37.98 LiCl@Ni2(dobpdc)-5 8248.73 1803.70 4.57 35.10

[0065] Next, to verify the change in the pore environment after the introduction of LiCl, a nitrogen adsorption experiment was performed at 77 K, and the results are shown in Figure 10.

[0066] Figure 10 shows the nitrogen adsorption isotherms of LiCl@Mg2(dobpdc)-5, LiCl@Mn2(dobpdc)-5, LiCl@Co2(dobpdc)-5, and LiCl@Ni2(dobpdc)-5, as well as the pore distribution of Mg2(dobpdc) and LiCl@Mg2(dobpdc)-5 calculated from the nitrogen isotherms.

[0067] As shown in Fig. 10, in the case of LiCl@Mg2(dobpdc)-5, the nitrogen adsorption amount decreased compared to Mg2(dobpdc), but it maintained a Type IV adsorption curve shape similar to the nitrogen adsorption isotherm of Mg2(dobpdc). The pore volume was 1.32 cm³. 3 g -1 from 0.204 cm 3 g -1 It decreased, which is interpreted as a result of LiCl being introduced into the pores and occupying some of the space. However, analysis of the pore size distribution confirmed that the main pore structure of approximately 18.5 Å was still maintained. On the other hand, LiCl@Mn2(dobpdc)-5, LiCl@Co2(dobpdc)-5, and LiCl@Ni2(dobpdc)-5 showed a tendency for a significant decrease in nitrogen adsorption. This is attributed to LiCl being distributed more extensively inside the pores as well as on the outer surface of the framework, or partially occupying some pore channels.

[0069] Next, to confirm the effect of introduction according to the concentration of the lithium chloride solution, the PXRD patterns of Mg2(dobpdc), LiCl@Mg2(dobpdc)-3, LiCl@Mg2(dobpdc)-5, LiCl@Mg2(dobpdc)-7, and LiCl were measured, and the mass ratio (wt%) of the introduced lithium chloride was analyzed using ICP-AES, and the results are shown in Figure 11 and Table 2 below, respectively.

[0070] As shown in Figure 11, characteristic diffraction peaks of lithium chloride were observed in all samples of LiCl@Mg2(dobpdc)-3, LiCl@Mg2(dobpdc)-5, and LiCl@Mg2(dobpdc)-7. In addition, the position of the characteristic diffraction peak of Mg2(dobpdc) was maintained even when a relatively high concentration of 7 M LiCl solution was used, and through these results, it was confirmed that the collapse of the skeletal structure did not occur even under high concentration conditions.

[0071] In addition, as shown in the results of Table 2 below, the content of lithium chloride introduced into the skeleton gradually increased as the concentration of the LiCl solution increased, and through this, it was confirmed that the amount of LiCl introduced can be controlled by the solution concentration.

[0072] Li [mmol L -1 ] M [mmol L -1 ] Li / Mg atomic ratio wt%LiCl LiCl@Mg2(dobpdc)-3 7113.26 2973.58 2.39 40.59 LiCl@Mg2(dobpdc)-5 10270.57 2073.52 4.95 58.58 LiCl@Mg2(dobpdc)-7 11830.36 1944.10 6.09 63.47

[0075] Next, the distribution characteristics of LiCl were analyzed using scanning transmission electron microscopy (STEM) and elemental mapping using energy dispersive X-ray spectrometry (EDS), and the results are shown in Figures 12 and 13.

[0076] Figure 12 shows the elemental mapping images of C, O, Mg, and Cl using STEM-EDS for LiCl@Mg2(dobpdc)-3, LiCl@Mg2(dobpdc)-5, and LiCl@Mg2(dobpdc)-7. As shown in Figure 12, the Cl elemental signal was evenly distributed throughout the sample, suggesting that lithium chloride is dispersed throughout the entire framework without aggregating in specific regions. Furthermore, it was confirmed that the spatial distribution of Cl remained generally uniform despite differences in LiCl solution concentration.

[0077] Figure 13 shows the HRTEM image, Fast Fourier transform (FFT) pattern, and SAED pattern of LiCl@Mg2(dobpdc)-5. As shown in Figure 13, periodic lattice fringes were observed in the HRTEM image, and SAED pattern analysis confirmed a diffraction signal corresponding to a lattice fringe of approximately 0.30 nm. This is interpreted to be consistent with the value corresponding to the (111) crystal plane of lithium chloride. The FFT analysis results also supported the presence of crystalline LiCl. Through these results, it was confirmed that LiCl exists in the form of nano-sized crystalline particles within the framework and is relatively uniformly dispersed within the framework.

[0079] Next, to verify the change in pore environment according to the concentration of lithium chloride solution, nitrogen adsorption experiments were performed at 77 K, and the results are shown in Figure 14. In addition, the BET specific surface area and pore volume of LiCl@Mg2(dobpdc)-3, LiCl@Mg2(dobpdc)-5, and LiCl@Mg2(dobpdc)-7 were measured, and the results are shown in Table 3 below.

[0080] Figure 14 shows the nitrogen adsorption isotherms of LiCl@Mg2(dobpdc)-3, LiCl@Mg2(dobpdc)-5, and LiCl@Mg2(dobpdc)-7, and the pore distribution of LiCl@Mg2(dobpdc)-3 and LiCl@Mg2(dobpdc)-7 calculated from the nitrogen isotherms.

[0081] As shown in Figure 14 and Table 3, as the concentration of the LiCl solution used increased, the nitrogen adsorption amount, BET specific surface area, and total pore volume showed a tendency to gradually decrease. This is interpreted as being due to the LiCl introduced into the pores occupying a portion of the pore space. However, the pore size distribution analysis results showed that the main pore size of approximately 18.5 Å was maintained despite the increase in concentration, confirming that the skeletal structure itself is maintained even when the amount of LiCl introduced increases. In particular, in the case of LiCl@Mg2(dobpdc)-7, nitrogen adsorption was not lost despite a high lithium chloride mass ratio of approximately 63 wt%, confirming that the pore structure is maintained at a certain level.

[0082] BET surface area [m 2 g -1 ] Pore volume [cm 3 g -1 ] LiCl@Mg2(dobpdc)-3 995 0.337 LiCl@Mg2(dobpdc)-5 620 0.204 LiCl@Mg2(dobpdc)-7 450 0.155

[0084] LiCl@M 2 Analysis of the ammonia adsorption and desorption performance of (dobpdc)

[0085] To evaluate the ammonia adsorption performance of a metal-organic framework introduced with lithium chloride nanoparticles, the ammonia adsorption isotherm was measured at 298 K and the adsorption amount at 1 bar was compared, and the results are shown in Fig. 15.

[0086] Figure 15 shows the 298 K ammonia adsorption isotherms of LiCl@Mg2(dobpdc)-5, LiCl@Mn2(dobpdc)-5, LiCl@Co2(dobpdc)-5, LiCl@Ni2(dobpdc)-5, and LiCl.

[0087] As shown in Fig. 15, LiCl@M2(dobpdc)-5 exhibited an isothermal shape with three adsorption regions, similar to the ammonia complexation reaction characteristics of lithium chloride. This indicates a stepwise LiCl(NH3) with increasing ammonia pressure. n (n = 1-3) This is interpreted to be due to the progression of complex formation. The adsorption amount of each sample at 1 bar is as follows: LiCl@Mg2(dobpdc)-5 (48.3 mmol g -1 ), LiCl@Mn2(dobpdc)-5 (37.8 mmol g -1 ), LiCl@Co2(dobpdc)-5 (59.5 mmol g -1 ), LiCl@Ni2(dobpdc)-5 (42.5 mmol g -1 ). On the other hand, due to its low specific surface area, lithium chloride has Li exposed on the surface + and Cl - Since only 3.47 mmol g is involved in adsorption -1 It showed a very low adsorption amount.

[0088] In addition, the adsorption stages for each sample were analyzed according to pressure ranges, and the results are shown in Table 4 below.

[0089] As shown in Table 4, the ammonia adsorption of LiCl@M2(dobpdc)-5 is broadly divided into three stages. The first adsorption stage occurs in the low-pressure region and is attributed to the coordination adsorption of ammonia by the open metal sites (OMS) of the framework. The second adsorption stage is observed in the intermediate-pressure region and is the stage where the formation of LiCl(NH3) complexes is initiated in the LiCl nanoparticles dispersed within the framework. The third adsorption stage occurs in the higher-pressure region and corresponds to additional ammonia adsorption following the formation of higher-order complexes such as LiCl(NH3)3. Such stepwise adsorption behavior suggests that the framework according to the present invention possesses a storage mechanism based on chemical complexation reactions, distinct from simple physical pore adsorption.

[0090]

[0092] Next, to confirm the formation of the LiCl(NH3)4 complex, the ammonia adsorption isotherm for LiCl@Mg2(dobpdc)-5 and lithium chloride was measured at 273 K, and the results are shown in Fig. 16 below. Optical images of the volume change after ammonia injection were measured, and the results are shown in Fig. 17 below.

[0093] Figure 16 shows the 273K ammonia adsorption isotherm of LiCl@Mg2(dobpdc)-5, LiCl.

[0094] As shown in Figure 16, lithium chloride showed a rapid change in adsorption amount at 540 mbar or higher, and it was confirmed that this was due to the formation of LiCl(NH3)4 complexes. On the other hand, LiCl@Mg2(dobpdc)-5 showed an additional adsorption step at 600 mbar or higher, and it was confirmed that LiCl(NH3)4 complexes were also formed in the lithium chloride-containing framework.

[0095] Figure 17 shows an optical image of the volume change of LiCl@Mg2(dobpdc)-5, LiCl at 273K after ammonia injection.

[0096] As shown in Fig. 17, lithium chloride exhibited significant volume expansion after ammonia adsorption. This is interpreted to be due to changes in crystal structure and swelling phenomena resulting from the formation of higher-order ammonia complexes. On the other hand, in the case of LiCl@Mg2(dobpdc)-5, macroscopic volume changes of the sample were observed to be relatively limited even after ammonia injection. This is interpreted to be because LiCl is uniformly dispersed at a nano-scale within the framework, so the expansion stress generated during the complexation reaction is distributed throughout the entire structure. Through these results, it was confirmed that the lithium chloride-containing porous metal-organic framework of the present invention has the potential to serve as an ammonia storage material capable of forming higher-order ammonia complexes while maintaining structural stability.

[0098] Next, to analyze the ammonia adsorption performance according to the lithium chloride content in the Mg2(dobpdc) framework, the ammonia adsorption isotherms of LiCl@Mg2(dobpdc)-3 and LiCl@Mg2(dobpdc)-7 were measured, and the results are shown in Fig. 18 below.

[0099] Figure 18 shows the 273 K ammonia adsorption isotherms of LiCl@Mg2(dobpdc)-3, LiCl@Mg2(dobpdc)-5, and LiCl@Mg2(dobpdc)-7.

[0100] As shown in Fig. 18, all samples exhibited three adsorption phases, consistent with the previously described method, which is attributed to the formation of LiCl(NH3)(n = 1-3) complexes. The adsorption amount of each sample at 1 bar is as follows: LiCl@Mg2(dobpdc)-3 (38.2 mmol g -1 ), LiCl@Mg2(dobpdc)-7 (44.8 mmol g -1).

[0101] Furthermore, in the case of LiCl@Mg2(dobpdc)-7, the adsorption capacity tended to decrease even at a higher lithium chloride mass ratio compared to LiCl@Mg2(dobpdc)-5, but it still maintained excellent ammonia adsorption performance and stepwise complexation characteristics. Through this, it was confirmed that the complexation reaction with ammonia can proceed effectively even when lithium chloride nanoparticles are dispersed within the framework.

[0103] LiCl@Mg 2 Evaluation of Ammonia Adsorption / Desorption Cycle and Stability of (dobpdc)-5

[0104] Reusability and stability against ammonia were evaluated by conducting repeated ammonia adsorption and desorption cycle measurements on LiCl@Mg2(dobpdc)-5 at 298 K, and the results are shown in Figure 19 below.

[0105] Figure 19 shows the repeated adsorption and desorption ammonia adsorption isotherm of LiCl@Mg2(dobpdc)-5 (left) and the amount of ammonia adsorbed at 1 bar (right).

[0106] As shown in Fig. 19, high ammonia adsorption performance was maintained without a significant decrease compared to the initial adsorption amount even after a total of five repeated adsorption and desorption cycles. In addition, the three adsorption stages were observed identically even after the repeated cycles, which indicates that LiCl(NH3) nIt was confirmed that the ignition-based stepwise adsorption mechanism is maintained even during repeated processes. In addition, desorption was performed after 6 hours of treatment under vacuum conditions at 373 K, and it was found that ammonia was effectively removed under these conditions and adsorption performance was recovered in subsequent cycles. This demonstrates that structural stability and functional adsorption characteristics can be maintained even under relatively relaxed regeneration conditions. Through these results, it was confirmed that the porous metal-organic framework with lithium chloride introduced according to the present invention can maintain excellent performance even during repeated ammonia adsorption and desorption processes, and thus can be usefully utilized as an ammonia storage material.

[0108] LiCl@Mg 2 Evaluation of the ammonia storage capacity of (dobpdc)-5

[0109] To evaluate the potential for use as an ammonia storage medium, the ammonia storage capacity per unit volume of the adsorbent was calculated, and to examine its potential as a hydrogen carrier, an indirect hydrogen storage capacity was calculated based on the weight-based ammonia adsorption amount at 298K and 1 bar, and the results are shown in Figure 20.

[0110] As shown in Fig. 20, the volumetric ammonia storage capacity of LiCl@Mg2(dobpdc)-5 is 65.8 mmol cm⁻¹ at 298 K. -3 , 109.1 mmol cm at 273 K -3 It was calculated as (Fig. 20, left). This corresponds to a very high level of volumetric storage capacity compared to previously reported porous adsorbents. Converted to mass density, the ammonia storage density is 1.12 g cm⁻³ at 298 K. -3 , 1.86 g cm at 273K -3 It was calculated as follows. This value is 0.817 g cm³, which is the density of solid ammonia at 193 K. -3 It corresponds to a higher value, and this is not due to simple physical adsorption within the pores but to LiCl(NH3) nIt is believed to be due to chemical absorption behavior based on complex formation.

[0111] In addition, based on the amount of ammonia adsorbed at 298K and 1 bar, the amount of hydrogen that can be released in the presence of an ammonia decomposition catalyst was calculated, and the indirect weight-based hydrogen storage capacity was found to be approximately 14.6 wt%. This corresponds to a high level compared to reported porous adsorbent-based hydrogen storage systems and is close to the theoretical hydrogen storage capacity of ammonia itself (17.8 wt%) (Fig. 20, right).

[0112] Through these results, it was confirmed that the porous metal-organic framework with lithium chloride introduced according to the present invention exhibits high volume and weight-based ammonia storage characteristics, and can be usefully utilized as an ammonia-based hydrogen carrier system.

[0114] LiCl@Mg through dynamic breakthrough experiments 2 Evaluation of the dynamic ammonia adsorption performance of (dobpdc)-5

[0115] To verify the dynamic ammonia adsorption performance, breakthrough experiments were conducted under conditions of 298K and 10% NH3. To verify the continuous dynamic adsorption performance, three repeated cycles were performed, and the results are shown in Figure 21 below.

[0116] Figure 21 shows the repeated cycle breakthrough curve of LiCl@Mg2(dobpdc)-5.

[0117] As shown in Figure 21, the shape of the breakthrough curve and the residence time remained similar without significant change in each cycle, confirming that the ammonia adsorption function is stably maintained even under dynamic flow conditions. In addition, desorption was performed after 12 hours of treatment under He flow conditions at 298K, and similar residence times were observed in subsequent re-adsorption experiments, confirming that dynamic adsorption characteristics can be repeatedly recovered even under relatively relaxed regeneration conditions.

[0118] Through these results, it was confirmed that the porous metal-organic framework with lithium chloride introduced according to the present invention can be usefully utilized as a reusable ammonia adsorption material not only for its high capacity characteristics in static adsorption isotherms but also under actual flow process conditions.

[0120] Mg 2 g-scale synthesis of (dobpdc) and LiCl@Mg 2 Synthesis and Characterization of (dobpdc)_G-5

[0121] Since it is important to reproducibly manufacture large-capacity adsorbents for practical applications, g-scale Mg2(dobpdc)_G was synthesized using the reflux method.

[0122] First, MgCl2·6H2O (3.0423 g, 15 mmol) was placed in a 250 mL two-necked round-bottom flask and connected to a reflux condenser. After being placed under vacuum for 1 hour, 60 mL of EtOH was added and stirred until the MgCl2·6H2O dissolved. H4dobpdc (1.37 g, 5 mmol) was placed in a 250 mL one-necked round-bottom flask, 60 mL of DMF was added, and the mixture was dissolved by sonication. The H4dobpdc solution was placed in a two-necked round-bottom flask and reacted by stirring at 130°C for 72 hours. After the reaction was complete, the resulting solid was filtered and washed with an excess of DMF and MeOH. Subsequently, the product and 100 mL of DMF were added to a 250 mL round-bottom flask and stirred at 50°C for 12 hours to remove unreacted H4dobpdc. The product was obtained by filtration, and the white solid was immersed in MeOH for 3 days and replaced with fresh MeOH at least 6 times. After 3 days, the solid was obtained by filtration again and vacuum dried for more than 12 hours to obtain white Mg2(dobpdc)_G.

[0123] Mg2(dobpdc)_G synthesized on a g-scale was activated at 180°C under vacuum conditions for 12 hours. 10 mL of 5 M lithium chloride methanol solution and 100 mg of activated M2(dobpdc)_G were weighed and added to a 20 mL vial. A magnetic stirrer was inserted, and the reaction was carried out while stirring at room temperature. After 3 hours of reaction, the resulting solid was filtered and obtained, and the obtained solid was vacuum dried for more than 12 hours to obtain LiCl@Mg2(dobpdc)_G-5.

[0125] Next, powder X-ray diffraction (PXRD) was performed on Mg2(dobpdc)_G and LiCl@M2(dobpdc)_G-5, and the results are shown in Fig. 22 below.

[0126] Through the results of Figure 22, Mg2(dobpdc)_G exhibited diffraction peaks consistent with the characteristic diffraction pattern of the original Mg2(dobpdc), confirming that the crystallinity of the framework was maintained even after g-scale synthesis. In addition, in the case of LiCl@Mg2(dobpdc)_G-5, while the main diffraction peaks of the framework were maintained, a characteristic Bragg diffraction peak attributable to lithium chloride was additionally observed, thereby confirming that lithium chloride was successfully introduced into the framework prepared on a g-scale.

[0128] LiCl@Mg 2 Analysis of the ammonia adsorption performance of (dobpdc)_G-5

[0129] The ammonia adsorption isotherm of LiCl@Mg2(dobpdc)_G-5 at 298K was measured to evaluate the adsorption performance at 1 bar, and the results are shown in Fig. 23 below.

[0130] Figure 23 shows the 298 K ammonia adsorption isotherm of LiCl@Mg2(dobpdc)_G-5.

[0131] As shown in Fig. 23, LiCl@Mg2(dobpdc)_G-5 exhibited three adsorption stages similar to the small-scale synthetic sample LiCl@Mg2(dobpdc)-5, which is LiCl(NH3) n This suggests that stepwise adsorption behavior attributed to complex formation is maintained even in g-scale synthesized samples. The ammonia adsorption capacity at 1 bar is 46.8 mmol g -1 It was measured as such, which corresponds to an adsorption performance level similar to that of small-scale synthetic samples. These results demonstrate that the structural characteristics of the framework and the dispersion state of lithium chloride nanoparticles are effectively maintained even during the g-scale synthesis process. Through these results, it was confirmed that the porous metal-organic framework with lithium chloride according to the present invention can maintain ammonia adsorption characteristics even after scale expansion, making large-scale production for actual applications possible.

[0133] Synthesis and Characterization of LiCl@MOF-74(Mg)-5, LiCl@MIL-101(Cr)-5, and LiCl@UiO-66(Zr)-5

[0134] To verify the introduction of lithium chloride into MOF templates other than the M2(dobpdc) framework, which possesses hexagonal one-dimensional channels, and the resulting ammonia adsorption performance, lithium chloride was introduced into three representative MOFs: MOF-74 (Mg), MIL-101 (Cr), and UiO-66 (Zr). A 5 M lithium chloride methanol solution was prepared, and MOF-74 (Mg) and MIL-101 (Cr) were activated for 12 hours under vacuum conditions at 180°C, while UiO-66 (Zr) was activated under vacuum conditions at 150°C. 10 mL of the lithium chloride methanol solution and 100 mg of each activated MOF were weighed and placed in a 20 mL vial. A magnetic stirrer was inserted, and the reaction was carried out while stirring at room temperature. After 3 hours of reaction, the resulting solid was filtered and collected; the obtained solid was vacuum dried for more than 12 hours and then stored.

[0135] Next, the introduced lithium chloride was identified using inductively coupled plasma atomic emission spectroscopy (ICP-AES), and the atomic ratio of Li / Metal was calculated and the results are shown in Table 5 below.

[0136] According to Table 5, the Li / Mg atomic ratio for LiCl@MOF-74(Mg)-5 was found to be 1.43. This corresponds to a relatively low introduction amount compared to Mg2(dobpdc)-based samples synthesized under the same conditions. This difference may be attributed to differences in pore size, channel connectivity, and internal surface chemical environment of the framework structure. Meanwhile, the Li / Metal atomic ratios for LiCl@MIL-101(Cr)-5 and LiCl@UiO-66(Zr)-5 were found to be 5.30 and 5.85, respectively, which correspond to introduction ratios similar to those of Mg2(dobpdc)-based samples. These results suggest that the introduction strategy of lithium chloride nanoparticles is applicable to various porous MOF structures.

[0137] Li [mmol L -1 ] M [mmol L -1 ] Li / Metal atomic ratio LiCl@Mg-MOF-74-5 8892.89 3313.88 1.43 LiCl@MIL-101-5 6388.47 1205.64 5.30 LiCl@UiO-66-5 4723.66 1520.33 5.85

[0139] Analysis of Ammonia Adsorption and Desorption Performance of LiCl@MOF-74(Mg)-5, LiCl@MIL-101(Cr)-5, and LiCl@UiO-66(Zr)-5

[0140] To evaluate the ammonia adsorption characteristics of LiCl@MOF-74(Mg)-5, LiCl@MIL-101(Cr)-5, and LiCl@UiO-66(Zr)-5, the ammonia adsorption isotherm was measured at 298K and the adsorption amount at 1 bar was analyzed, and the results are shown in Figure 24 below.

[0141] Figure 24 shows the ammonia adsorption isotherms at 298 K for LiCl@MOF-74(Mg)-5, LiCl@MIL-101(Cr)-5, and LiCl@UiO-66(Zr)-5.

[0142] As shown in Fig. 24, in the case of LiCl@MOF-74(Mg)-5, due to the relatively low content of introduced lithium chloride, no clear three-stage adsorption behavior attributable to lithium chloride-based complexation reactions was observed. This suggests that even though Mg-MOF-74 possesses a one-dimensional hexagonal channel structure similar to Mg2(dobpdc), the internal dispersion and high-content introduction of lithium chloride may be limited due to its relatively small pore diameter. On the other hand, LiCl@MIL-101(Cr)-5 and LiCl@UiO-66(Zr)-5 were characterized by three-stage adsorption curves, and the adsorption amount at 1 bar was measured as follows: LiCl@MIL-101(Cr)-5 (40.05 mmol g⁻¹). -1 ), LiCl@UiO-66(Zr)-5 (35.79 mmol g -1 ).

[0143] In particular, UiO-66(Zr) has a BET specific surface area similar to that of Mg-MOF-74, but forms a three-dimensional pore structure with connected octahedral and tetrahedral cages, possessing structural characteristics that allow lithium chloride to be dispersed more uniformly. Through this, it was confirmed that pore shape and connectivity, rather than simple specific surface area, have a significant influence on the lithium chloride introduction efficiency and adsorption behavior.

[0144] Furthermore, the above results demonstrate that metal halide nanoparticles can be effectively introduced into various metal-organic frameworks. Additionally, it was confirmed that the metal-organic framework according to the present invention can be usefully utilized as an ammonia adsorbent and storage material, as it exhibits high-capacity ammonia adsorption based on metal-ammine complexation reactions, limited volume expansion even after complex formation, the possibility of desorption under relatively mild conditions, and stable adsorption-desorption behavior upon repeated use.

[0146] Foregoing, specific parts of the present invention have been described in detail. It will be apparent to those skilled in the art that such specific descriptions are merely preferred embodiments and do not limit the scope of the invention. Accordingly, the actual scope of the invention is defined by the appended claims and their equivalents.

Claims

Claim 1 An ammonia adsorbent comprising: a porous metal-organic framework; and a metal halide introduced into the pores or surface of the porous metal-organic framework. Claim 2 The ammonia adsorbent according to claim 1, wherein the porous metal-organic framework is selected from the group consisting of M2(dobpdc), M2(dobdc), M2(m-dobdc), M2(dondc), and M2(dotpdc): wherein metal M is Mg, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, or Zn, dobpdc is 4,4'-dioxido-3,3'-biphenyldicarboxylate, dobdc is 2,5-dioxido-1,4-benzenedicarboxylate, m-dobdc is 4,6-dioxido-1,3-benzenedicarboxylate, dondc is 1,5-dioxido-2,6-naphthalenedicarboxylate, and dotpdc is 4,4'-dioxido-3,3'-triphenyldicarboxylate. Claim 3 The ammonia adsorbent according to claim 1, wherein the porous metal-organic framework is selected from the group consisting of MIL-100, MIL-101, MIL-121, MIL-127, MIL-53, UiO-66 and UiO-67. Claim 4 An ammonia adsorbent according to claim 1, characterized in that the metal halide is an alkali metal halide. Claim 5 An ammonia adsorbent according to claim 4, characterized in that the alkali metal is one or more selected from the group consisting of lithium (Li), sodium (Na), potassium (K), rubidium (Rb), and cesium (Cs). Claim 6 An ammonia adsorbent according to claim 1, characterized in that the content of the metal halide is 30 to 70 weight%. Claim 7 An ammonia adsorbent according to claim 1, characterized by exhibiting stepwise adsorption behavior induced by the formation of a complex between ammonia and a metal halide. Claim 8 An ammonia storage system comprising an ammonia adsorbent according to paragraph 1.